Determining the distribution of temperature fields in construction elements of shell-and-tube heat exchangers using analytical and numerical heat and hydraulic calculations - Pyrohov, Tymofii; Korolev, Alexander (Technology audit and production reserves, 2020)
The object of research is numerous and analytical thermohydraulic calculations of a shell-and-tube heat exchanger of a counterflow type. To determine the thermally stressed state of heat exchangers, calculations of the temperature fields of their elements are performed. At the same time, it is not a trivial task to perform numerical thermohydraulic calculations for a heat exchanger that has a large number of heat exchange tubes. This statement is due to the fact that the calculation model will contain a large number of finite elements. Difficulties in performing these calculations may arise when using electronic computers with limited technical parameters. Such calculations may take quite a long time, or may not be performed at all. The authors proposed an approach to determining the temperature fields in individual elements of a heat exchanger. It consists of a combination of analytical and numerical thermohydraulic calculations of individual elements of the heat exchanger and the internal bodies in contact with them. This allows to reduce the time and bit depth of calculations. To validate the above-mentioned approach, two calculation models of a shell-and-tube heat exchanger of a counterflow type were built. As the first calculation model, the entire body of the heat exchanger was constructed, taking into account the bodies of its coolant and cooling water. For this model, only numerical thermohydraulic calculations were performed. As the second calculation model, a part of the heat exchanger was built, taking into account all the bodies of the coolant and cooling water, belonging to it. With the help of analytical thermal calculations, the temperatures at the inlet to the shell-and-tube spaces of the second design model were determined. Subsequently, the results obtained analytically served as boundary conditions for performing numerical thermohydraulic calculations. As a result of the calculations performed, a comparison of the obtained results of the distribution of temperature fields in the above-mentioned calculation models is made. Based on the analysis of the results, it was concluded that it is possible to use a combined method (a combination of analytical and numerical thermohydraulic calculations) for determining the temperature fields in individual elements of heat exchangers.